Formation of ZnO/CuO Heterostructures Based on Quasi-One-Dimensional Nanomaterials - Serguei P. Murzin (Applied Sciences, 2022)
Nanostructured metal oxides are of great interest both for advanced research and for a wide range of applications that contribute to the increasing demands of electronics, photonics, catalysis, sensorics, and other high-tech industries and are being actively researched and developed. One-dimensional nanocrystal arrays of copper and zinc oxides have become prominent in optoelectronic devices and energy conversion systems. However, although desirable improved properties have been demonstrated, the morphology of materials containing copper and zinc oxide nanowires is extremely sensitive to synthesis conditions and difficult to control. Studies focused on the morphology control of such quasi-one-dimensional materials are not numerous, so the consideration of this issue is still relevant. The characteristics of devices based on such oxide materials can be improved by taking advantage of nanoheterojunctions. A special feature is the possibility of forming a polycrystalline heterojunction in a system of semiconductors belonging to different crystalline syngonies. Currently, much attention is devoted to developing reliable methods of obtaining such nanomaterials, including those, based on processes exploiting novel physical effects. Possibilities of synthesis by pulse-periodic laser irradiation of arrays of quasi-one-dimensional ZnO nanostructures with varying micromorphology on metallic substrates, as well as the creation of ZnO/CuO heterostructures based on ZnO nanowires, were considered. The main distinguishing feature of this approach was the use of laser-induced vibrations to intensify diffusion processes in the solid phase of metallic materials as compared to the simple effects of laser beam heating. Expanding the area of application of the advanced method of creating oxide heterostructures requires a detailed and comprehensive study of new possibilities used to form structures with improved physical properties.